Kinesio taping to address post-sternotomy scars in pediatric patients: A case report - Elizabeth G Harvey (SAGE Publishing, 2022)
Introduction The role of postoperative scar tissue adhesion and its impact on motor control in infants with congenital heart disease has not been explored in the literature. Elastic therapeutic tapes, such as Kinesio tape, are designed to affect the integumentary system. This case report aims to demonstrate the safety and present the observations following use of Kinesio tape to treat scar tissue in a pediatric patient after open-heart surgery in conjunction with standard rehabilitation. Method This retrospective case report presents observations of an infant's sternotomy scar adhesion and gross motor development after six applications of Kinesio tape. The sternotomy and drain tube scars were treated with Kinesio tape fascia applications in addition to standard physical therapy (PT). Discussion Several domains showed positive changes. The scar mobility and appearance improved. The patient's motor skills improved, possibly due to skin stretch's role in motor learning. The taping application did not cause discomfort, and there were no adverse reactions. Conclusion In this infant, the three-month-old sternotomy scar improved in adherence and appearance after six applications of Kinesio Fingerprint tape; motor skills also increased in the presence of standard PT. There were no adverse reactions noted with the protocol. Kinesio tape may provide a safe adjunct to treat scar tissue adhesion in infants with median sternotomy scars. Lay Summary Issue being explored Sternotomy scars can cause physical and psychological harm. Sensors (receptors) in the skin help with movement and balance responses. The impact of scar stiffness (adhesion) on developing motor control has not been reported in infants. Treating the scar in the remodelling phase with elastic tape may improve the scar's appearance and ability to move, thereby improving development.